Unlocking Student Collaboration: Exploring the Power of Trello in Education - Reftyawati, Dian (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This paper presents a project focused on the development of school instruments within a school observation course, where students engaged in virtual collaboration and discussions across different classes utilizing the Trello application. Employing a narrative inquiry design, this study examines the experiences of a teacher over four months of teaching practice. Data were collected through teacher observation notes documenting the use of the Trello application during teaching practice, as well as interviews conducted with participants both in groups and individually within the school observation course. Subsequently, the data were analyzed using NVivo software. The narrative analysis evaluates the effectiveness and contribution of the Trello application as a reflective tool to enhance students’ active collaboration. The findings indicate that student collaboration using the Trello application over the four-month period demonstrated a high level of engagement. The application’s innovative and user-friendly features facilitated dynamic discussions. The students’ enthusiasm affirmed the teacher’s perception that the Trello application serves as an effective platform for fostering collaboration and virtual discussion to produce project outcomes. A significant conclusion from this research is that the Trello application has the potential to be employed as an online learning tool or as an instructional medium that supports interventions aimed at improving collaborative efforts in educational contexts